Health status and public health education for internal older migrants in China: Evidence from a nationally representative survey - Zeng, Wen; Wang, Cui; Chen, Hongbo; Tong, Beibei; Li, Dan; Zou, Ziqiu; Liu, Peiyuan; Yao, Yuanrong; Shang, Shaomei (Frontiers in Public Health, 2022)
Background: Under the context of the rapid growth of aging, there was a dramatic rapid expansion in internal older migrants in China. Most of the previous studies focus on the utilization of public health services such as visiting to doctors, physical examination, hospitalization. There was limited evidence on the self-rated health and public health education of older migrants. Objectives: The study aimed to evaluate self-rated health and the associated factors in older migrants. Another aim of the study was to better understand the current status of public health education received by older migrants. Methods: We derived the data from the National Migrants Population Health and Family Planning Dynamic Monitor Survey 2018, a cross-sectional study, for secondary analysis. Internal migrants aged 60 years old or over were included in the study. Self-rated health was the dependent variable, while sociodemographic characteristics were the independent variables. The univariate and multivariate analyses were performed by Stata 15.1. Results: A total of 5589 older migrants were included in the study. 82.00% of older migrants reported healthy self-rated health. There was a significant association between age, gender, minzu, education level, monthly income, public health education and self-rated health (P<0.5). However, the proportion of older migrants that received specific PHE was less than 50%. The most common approach of receiving public health education was through the leaflet, while less than 20% of older migrants received public health education through public consultation and one-to-one education. Conclusions: It was necessary to promote the publicity of public health education in older migrants through easy access and diverse approaches in order to effectively spread health-related knowledge to older migrants to satisfy their health needs and maintain their health.